Lower Extremity Biomechanics Are Altered Across Maturation in Sport-Specialized Female Adolescent Athletes - DiCesare, Christopher A.; Montalvo, Alicia; Barber Foss, Kim D.; Thomas, Staci M.; Ford, Kevin R.; Hewett, Timothy E.; Jayanthi, Neeru A.; Stracciolini, Andrea; Bell, David R.; Myer, Gregory D. (Frontiers in Pediatrics, 2019)
Sport specialization, which may be considered year-round training in a single sport, is a growing trend in youth athletes. Early sport specialization may contribute to injury risk. The dynamic effects of maturation on reduced neuromuscular control may be amplified in young athletes who specialize in a single sport. The purpose of this study was to investigate if sport specialization is associated with increased proliferation of aberrant biomechanics during maturational development in adolescent female athletes. Seventy-nine sport-specialized female adolescent basketball, soccer, and volleyball athletes were identified and matched with seventy-nine multi-sport (soccer, basketball, and volleyball) female athletes from a database of 1116 female adolescent basketball, soccer, and volleyball athletes who were enrolled in one of two large prospective, longitudinal studies. The athletes were assessed over two visits in which they were classified as pre-maturational and post-maturational, respectively. Multivariate analysis of variance (MANOVA) was used to compare sport-specialized and multi-sport groups and dominant/non-dominant limbs with respect to maturational changes in peak sagittal, frontal, and transverse plane joint angular measures and joint moments of force for the hip and knee joints over the two visits. Kinematic changes through maturation showed no significant interaction with the group × limb and the main effects of group or limb (all p > .05). Kinetic changes through maturation showed no significant interaction with the group × limb and the main effect of limb (both p > .05). The main effect of group was significant (F(6, 152) = 3.196, p = .005). The sport-specialized group sustained a smaller increase in peak knee extensor moment than the multi-sport group (F(1, 157) = 5.658, p = .018) and exhibited a larger increase in peak knee abduction moment (F(1, 157) = 5.790, p = .017) when compared to the multi-sport group. Sport-specialized female athletes exhibited altered biomechanics during landing while performing the DVJ task compared to multi-sport athletes through maturation, which may play a role in injury risk profiles of sport-specialized female athletes.